Application of 2'-OMethylRNA' Antisense Oligomer to Control Candida albicans EFG1 Virulence Determinant - Daniela Araújo; Nuno Miguel Azevedo; Ana Barbosa; Carina Almeida; Maria Elisa Rodrigues; Mariana Henriques; Sónia Silva (Elsevier, 2019)
Antisense oligomers and their analogs have been successfully utilized to silence gene expression for the treatment of many human diseases; however, the control of yeast's virulence determinants has never been exploited before. In this sense, this work is based on the key hypothesis that if a pathogen's genetic sequence is a determinant of virulence, it will be possible to synthesize a nucleic acid mimic based on antisense therapy (AST) that will bind to the mRNA produced, blocking its translation into protein and, consequently, reducing the pathogen virulence phenotype. EFG1 is an important determinant of virulence that is involved in the regulation of the Candida albicans switch from yeast to filamentous form. Thus, our main goal was to design and synthesize an antisense oligonucleotide (ASO) targeting the EFG1 mRNA and to validate its in vitro applicability. The results show that the anti-EFG1 2'-OMethylRNA (2'OMe) oligomer was able to significantly reduce the levels of EFG1 gene expression and of Efg1p protein translation (both approximately 60%), as well as effectively prevent filamentation of C. albicans cells (by 80%). Moreover, it was verified that anti-EFG1 2'OMe keeps the efficacy in different simulated human body fluids. Undeniably, this work provides potentially valuable information for future research into the management of Candida infections, regarding the development of a credible and alternative method to control C. albicans infections, based on AST methodology. Keywords: Candidiasis, filamentation, nucleic acid mimics, 2'-OMethylRNA modification